LARVAL REARING AND SPAT PRODUCTION OF THE GREAT CLAM, MERETRIX MERETBJX (LINNAEUS) - Narasimham, K A; Muthiah, P; Gopinathan, C P; Gandhi, A D (Indian Journal of Fisheries, 2011)
The venerid clam Meretrix meretrix (Linnaeus) was spawned in the laboratory and for the first timethe eggs were reared successfully through various stages to spat. Setting was observed on day 7 andday 10 after fertilization and was mostly completed by day 9 and 12 respectively in the two experiments.The clam seed attained an average length of 2.895 mm and height of 2.475 mm on day 75. During therearing experiments the haptophycean flagellate, hochrysis galbana was given as food. In the lightof the results obtained here the thrust areas for standardising the procedures in the hatchery productionof the seed of M. meretrix are discussed.